2020
DOI: 10.1515/cog-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

Anger stinks in Seri: Olfactory metaphor in a lesser-described language

Abstract: Previous studies claim there are few olfactory metaphors cross-linguistically, especially compared to metaphors originating in the visual and auditory domains. We show olfaction can be a source for metaphor and metonymy in a lesser-described language that has rich lexical resources for talking about odors. In Seri, an isolate language of Mexico spoken by indigenous hunter-gatherers, we find a novel metaphor for emotion never previously described – “anger stinks”. In addition, distinct odor verbs are used metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Non-literal metaphorical use of smell language appears in some languages (e.g., Seri [80]) but not others (e.g., Jahai). What smell metaphors are used across languages and how common are they?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-literal metaphorical use of smell language appears in some languages (e.g., Seri [80]) but not others (e.g., Jahai). What smell metaphors are used across languages and how common are they?…”
Section: Discussionmentioning
confidence: 99%
“…For example, smell is used metaphorically to refer to knowledge in Luwo (Sudan) [70] and is used to describe the relationship between words as part of an avoidance register in Datooga (Tanzania) [79]. Seri (a hunter-gatherer language of Mexico) has an elaborate smell lexicon and a number of specific olfactory metaphors for emotions (e.g., being angry), dreams (e.g., having a nightmare), ingestion (e.g., detesting food), activities (e.g., doing something carelessly), relationships (e.g., leaving someone without family), and the weather (e.g., being bad weather) [80]. Intriguingly, a recent study found that English smell words are primarily used figuratively, not literally (e.g., I will not make a stink over it) [37].…”
Section: Box 2 Is the Connection Between Olfaction And Language Symmmentioning
confidence: 99%
“…While there is disagreement as to whether or not ‘universal’ metaphors exist due to the shared human experience of embodiment (cf. Kövecses 2006), it is widely acknowledged that at least some metaphors are very common across cultures because of embodiment (e.g., O’Meara and Majid 2020). Because embodied experience varies over time or place or by individual, the ways in which embodiment constrains metaphor usage and comprehension likewise varies (Littlemore 2019).…”
Section: Metaphor Theory and Researchmentioning
confidence: 99%